2002
DOI: 10.1078/0944-7113-00083
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral activity of Rwandan medicinal plants against human immunodeficiency virus type-1 (HIV-1)

Abstract: Selected plants used in Rwandan traditional medicine for the treatment of infections and/or rheumatoid diseases were investigated for antiviral activity in vitro against human immunodeficiency virus type-1 (HIV-1). Of the 38 tested 80% ethanolic extracts, belonging to plants of 21 different families only the extracts from the leaves of Aspilia pluriseta (Asteraceae) and Rumex bequaertii (Polygonaceae) had interesting selectivity indices (SI = ratio of the 50% cytotoxic concentration to the 50% effective antivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 9 publications
0
67
0
3
Order By: Relevance
“…25 Emodin is the main active principle in various medicinal plant species and exhibits biological activities such as anti-inflammatory, antibiotic, antiviral, immunosuppressive, and hepatoprotective. 26,27 Some studies have also reported a tranquilizing activity for extracts derived from plants of the Family Polygonaceae. 28 The results obtained with the genotoxicity tests of the extracts of C. mollis, under the experimental conditions described, indicate induction of DNA damage only at the highest concentration tested in SCGE and no genotoxicity in MNCtB.…”
Section: Discussionmentioning
confidence: 99%
“…25 Emodin is the main active principle in various medicinal plant species and exhibits biological activities such as anti-inflammatory, antibiotic, antiviral, immunosuppressive, and hepatoprotective. 26,27 Some studies have also reported a tranquilizing activity for extracts derived from plants of the Family Polygonaceae. 28 The results obtained with the genotoxicity tests of the extracts of C. mollis, under the experimental conditions described, indicate induction of DNA damage only at the highest concentration tested in SCGE and no genotoxicity in MNCtB.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this, the anti-viral efficacy of the documented plant species, either in vitro or in vivo was also verified from published literature. Therefore, this review draws heavily on the results of ethnobotanical surveys undertaken in contemporary sub-Saharan Africa on traditional medicines used to treat or manage HIV/AIDS opportunistic diseases [1][2][3][4][5][6][7][8][9][10][11][12][13], as well as secondary data collected through a review of 60 research reports, policy documents, reports from national, regional and international organizations, and conference papers published in scientific journals (53), books (4), theses (2) and one as an abstract.…”
Section: Thementioning
confidence: 99%
“…Ethnobotanical studies conducted in the following sub-Saharan African countries indicated that traditional healers and local communities extensively use medicinal plants to manage the effects of HIV/AIDS in Cameroon [2], Namibia [3,4], Rwanda [5], South Africa [6][7][8], Sudan [9], Tanzania [1,10] and Uganda [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the incidences of bacterial resistance to antibiotics have been reported because of their imprudent use (Robert & Moellering, 1998). Many medicinal plants and their constituents have been extensively studied for their biological activities and applications, including raw and processed potential as natural agents for food preservatives, pharmaceuticals, and alternative medicines (Chomnawang et al, 2005;Cos et al, 2002;Panossian et al, 2010;Rocha et al, 2005;Rota et al, 2008). Thai edible plants have demonstrated various biological activities such as cancer prevention, antidiabetic, and antimicrobial activities (Eidi et al, 2006;Lantz et al, 2005;Manosroi, 2005;Sindhu et al, 2011;Siripongvutikorn et al, 2005;Wannissorn et al, 2005).…”
Section: Introductionmentioning
confidence: 99%